Analisis Nilai-Nilai Tasawuf Dalam Lirik Lagu Pulang Karya For Revenge - Juhri Jaelani; Nurlatifah (STIKes Ibnu Sina Ajibarang, 2025)
Apart from being a method of cleansing the soul, Sufism is also a forum for improving deeds or actions in daily life. People sometimes ignore the quality of the practice of Islamic teachings themselves, that in every Islamic teaching there are Sufism values ​​that can be implemented and practiced. This research aims to analyze, explain and research more deeply the values ​​of Sufism contained in the lyrics of the song Pulang Karya from the music band For Revenge. This research uses a qualitative approach with a literature study method, namely by analyzing, reviewing, comparing and presenting data descriptively. The data sources in this research are the lyrics of the song Pulang Karya For Revenge and other relevant research sources such as research journals, research articles, books and so on. The results of the research show that the lyrics of the song Pulang Karya For Revenge contain Sufism values ​​that can be implemented in everyday life, such as in the lyrics There is no place as beautiful as home, There is no place as beautiful as there, I keep looking for direction. These lyrics can be interpreted as humans longing for the final goal of their life, namely the afterlife, because in Islam, life on earth is a field leading to the afterlife to achieve true happiness.